Why Sustainable Development Fails Without Ethical Public Governance Policies? - Resti Dian Luthviati; Nikolas Wicaksono Prakoso Putro; Dhika Sri Anggrahini (Lembaga Contrarius Indonesia, 2025)
Environmental, social, and governance principles have increasingly shaped contemporary approaches to corporate governance and sustainable development, reflecting heightened demands for ethical conduct, accountability, and long-term value creation. However, the effectiveness of these principles remains contingent upon the quality of public governance and regulatory coherence. This study aims to analyze the role of ethical public governance in supporting the implementation of environmental, social, and governance principles as an instrument for achieving sustainable development objectives. The research employs a normative juridical method, examining statutory frameworks, principles of administrative law, and governance policies related to corporate responsibility and sustainability. The findings demonstrate that the absence of specific and coherent regulatory frameworks, coupled with weaknesses in administrative accountability and ethical governance, significantly undermines the consistency and effectiveness of environmental, social, and governance implementation. The study further finds that corporations with clearly articulated values, strategic vision, and institutional capacity are better positioned to integrate sustainability into long-term governance frameworks, particularly through corporate social responsibility programs. In this context, higher education initiatives emerge as a strategic form of corporate social responsibility, contributing to the development of sustainability-oriented leadership and innovation. The study concludes that ethical public governance constitutes a fundamental prerequisite for aligning corporate governance practices with sustainable development goals, and that strengthened administrative frameworks are essential to ensure durable and meaningful sustainability outcomes.